Income Inequality Tolerance and Preferences for Redistribution in Turkey (European Journal of Marketing and Economics, 2023)
In this paper, the extent to which redistribution is desired by the Turkish and its determinants are estimated. For this purpose, the 2009 Social Inequality Module of the International Social Survey Programme is used. Finding the attitudinal differences between urban and rural region residents, and understanding whether these can be attributed to educational differences is additionally aimed. The estimations indicate that pro-redistribution preferences are shaped by distributive justice considerations captured by the question on just payment at work. Having no or low educational qualification, living in urban regions and small cities also play an important role. Being in the lowest income categories is also associated with higher demand for redistribution. The attitudinal difference between rural and urban residents cannot be attributed to differences in the educational levels, differences in cultural values and/or income levels seem to play an important role. This study’s finding that women are more tolerant of income inequality than men is the opposite of the previous finding based on the 2011 WVS data, and of the more usual finding in other studies. Hard work has a non- significant effect in the present study although it was one of the determinants of pro-redistribution preferences previously. The impact of income is similar to previous analysis’ finding. However, mixed results were found in the previous analysis relative to the effect of living in a specific region. The effects are more homogeneous with ISSPA data, as all of the regions with significant coefficients have relatively reduced support for redistribution than Istanbul.
Keywords: Preferences for Redistribution, Turkey, International Social Survey Programme